An Efficient Ant Colony Algorithm Based on Rank 2 Matrix Approximation Method for Aircraft Arrival/Departure Scheduling Problem - Xu, Bo; Ma, Weimin; Ke, Hua; Yang, Wenjuan; Zhang, Hao (Processes, 2022)
The Aircraft Arrival/Departure Problem (AADSP) is the core problem in current runway system, even has become the bottleneck to prevent the improvement of the airport efficiency. This paper studies the single runway AADSP. A Mixed Integer Programming (MIP) model is constructed and an algorithm named Ant Colony based on Rank 2 Matrix Approximation (RMA-AC) method is proposed. Numerical results validate that the new algorithm, as well as the new model, exhibits better performance than CPLEX and the traditional two-phase algorithm. The runway efficiency enhanced by RMA-AC, within 20 s computation, is about 2–5% even for the 800 aircraft sequences. It is a promising method to improve the efficiency of the future aircraft scheduling system.